Problem-based Learning in Basic Physics — VI - Mody, A.K.; Pradhan, H.C. (SCHOOL SCIENCE, 2014)
In this article, sixth in the series, we present problems for a problem-based learning course from the area of quantum physics and nuclear physics. We present the learning objectives in this area of basic physics and what each problem tries to achieve with its solution